Pengaruh LDR dan BOPO terhadap ROA pada Bank Umum Swasta Nasional Devisa di Bursa Efek Indonesia - Delsi Indi Rahmawati; Diharpi Herli Setyowati; Fatmi Hadiani (Indonesian Journal of Economics and Management, 2021)
The purpose of this research is to find out the effect of Loan to Deposit Ratio (LDR), Operational Efficiency Ratio (OER) to Return on Asset (ROA) BUSN Devisa listed on Indonesian Stock Exchange (IDX) periode of 2012-2019. The population of this research are BUSN Devisa listed on Indonesian Stock Exchange (IDX), the sample of this research are 17 banks used purposive sampling methods. The analysis used in this research is panel data regression by using EVIEWS 9. The research showed that LDR partially has no effect and not significant to ROA, OER partially has significant effect to ROA, and simultaneously LDR and OER have significant effect to ROA.